BUILDING A SYSTEM FOR MONITORING AND CONTROLLING POLLUTION OF WATER BODIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Unregulated waste disposal is becoming increasingly widespread throughout our planet. Waste of various types is being dumped - plastic, glass, nylon, construction waste and others, which decompose very slowly and cause irreversible pollution and changes in the environment. These illegal dumps are particularly dangerous when they are located near water bodies or in the catchment area of drinking sources that supply settlements. The fight against these illegal dumps is still not at the required level and decisive measures are needed to limit them. The report presents a principle scheme for building a system for controlling the catchment areas of large sources of drinking water, which can be implemented very easily and quickly. This will help reduce environmental pollution near water bodies, groundwater and catchment areas of drinking sources. As a consequence, the risk of floods, landslides and other phenomena resulting from the impact of this waste will be reduced.